On Contradictions: The Architecture of Women’s Resistance and Emancipation in Early twentieth-Century Iran - Armaghan Ziaee (ABE Journal, 2020)
The public spaces in Iran’s built environment were gendered sites of domination and subordination, yet also terrains of resistance and emancipation. Tracing the massive western-oriented project of modernization of public spaces issued by the Shah of Iran, Reza Shah Pahlavi (1925-1941), this article contextualizes the gendered language used to advance modernization, and examines examples of women’s experiences in major cities including Tehran, Shiraz, Qazvin, Rasht, and Bushehr. During this period, modern architecture and planning movements in Iran mainly followed the discourse instigated by ciam [International Congresses of Modern Architecture]. Urban street plans with an orthogonal network of roads, streets, and wide boulevards were favored over the vernacular system of narrow, twisting, partly-roofed alleys, based on pedestrian movements. The modern movement also attempted to desegregate and “democratize” public spaces through gender desegregation, arguing that streets needed to be aesthetically-pleasing spaces where both men and women could walk and socialize in mixed-sex gatherings, a phenomenon that was not common in public spaces in the history of Iran. It should be noted that in 1936, Reza Shah promulgated a ban on the use of the chador (the traditional Iranian veil) in public places, in favor of Western women’s fashion, i.e., European hats, coats, and gloves. Due to this ban, some women, particularly those from conservative, religious, lower-class backgrounds, resisted using public spaces and streets. In older neighborhoods, where houses were attached to each other, these women used the rooftops as gathering spaces and as a form of pedestrian pathway. Others, mainly elite, urban, upper-class women, accepted and appreciated the desegregated spatial practices, using them to free themselves from social and cultural taboos. Building on postcolonial and transnational feminist theories, including those of Chandra Talpade Mohanty (1984) and Inderpal Grewal and Caren Kaplan (1994), which critique modernity and modernization and emphasize the diversity of women’s experiences and the importance of contextualizing them, this article addresses how, in a political climate of enormous contradictions, architectures were (re)configured and (re)appropriated as physical tools of resistance against the coloniality of modernization of the built environment and state power for one group of women, yet simultaneously, were (re)envisioned as an apparatus of confrontation with cultural traditionalism and patriarchal ideologies for another group of women.